Um modelo de otimização multiobjetivo aplicado no dimensionamento da capacidade instalada de uma Pequena Central Hidrelétrica - Ferreira, Jacson Hudson Inácio (2020)
or a Small Hydroelectric Plant (SHP), the careful sizing of the installed capacity is one of the most important issues for the elaboration of the basic project, with analyses to estimate the hydroelectric potential and to plan the operation system of the plant. In other words, capacity sizing specifies the profitability of the investment and the energy performance of the SHP. Currently, hydroelectric systems are in the optimization phase of the exploration in order to increase the power generation based on the same amount of energy coming from the natural resource. In this context, the present thesis aims to develop a multiobjective optimization model for the sizing of installed capacity in SHPs, considering the maximization of net benefit and the maximization of energy availability. For this purpose, the NSGA II and Multiobjective Differential Evolution (MODE) are applied and the results obtained for each optimization algorithm are compared. A case study was developed in the Tijuco River hydrographic basin, in the municipality of Ituiutaba – MG, applying the developed model. The results indicate that the functions are conflicting, the Differential Evolution has the results with a better convergence for the case study and the technical and economic characteristics of the SHP obtained dimensions in accordance with the purpose of the project.